Educational Robotics - Lim, Kelvin Wee Chong (Nanyang Technological University, 2023)
Unmanned aerial vehicles (UAVs), also known as drones, have gained immense popularity in recent years due to their diverse applications in various industries. These remotely piloted aircraft have a broad range of capabilities, including aerial surveillance, mapping, disaster management and cargo transportation . In today's world of artificial intelligence and automation, possessing computational thinking skills is highly valuable . We believe that the most effective way to develop these skills is through platforms that integrate practical hardware and compute r logic activities. The objective of this project is to create an intuitive software interface that will support the UAV project. The aim of this project is to provide an opportunity for individuals interested in building a UAV, even without a background in engineering. The project is primarily geared towards primary and secondary school students. Through the creation of this course ware, we hope to help these students discover their interests and passions earlier, empowering them to make more informed decisions regarding their future career paths.